2011
DOI: 10.1103/physrevb.83.165101
|View full text |Cite
|
Sign up to set email alerts
|

Coherent and incoherent dynamics in excitonic energy transfer: Correlated fluctuations and off-resonance effects

Abstract: We study the nature of the energy transfer process within a pair of coupled two-level systems (donor and acceptor) subject to interactions with the surrounding environment. Going beyond a standard weak-coupling approach, we derive a master equation within the polaron representation that allows for the investigation of both weak and strong system-bath couplings, as well as reliable interpolation between these two limits. With this theory, we are then able to explore both coherent and incoherent regimes of energ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
103
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 78 publications
3
103
0
Order By: Relevance
“…The results from the multi-electron/exciton models, which unlike one-electron/exciton models allow us to control the amount of strong electron correlation in the chromophores, are consistent with the notion that strong electron correlation is likely employed by nature to enhance its energy-transfer efficiency as much as other factors such as (i) environmental noise [5][6][7][8][9][10] and (ii) entanglement between chromophores [11][12][13], which have been extensively studied in the recent literature. In the multi-electron/exciton model the correlation of electrons within a molecular subunit like a chromophore is intrinsically connected with the entanglement of electrons between molecular subunits.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results from the multi-electron/exciton models, which unlike one-electron/exciton models allow us to control the amount of strong electron correlation in the chromophores, are consistent with the notion that strong electron correlation is likely employed by nature to enhance its energy-transfer efficiency as much as other factors such as (i) environmental noise [5][6][7][8][9][10] and (ii) entanglement between chromophores [11][12][13], which have been extensively studied in the recent literature. In the multi-electron/exciton model the correlation of electrons within a molecular subunit like a chromophore is intrinsically connected with the entanglement of electrons between molecular subunits.…”
Section: Introductionsupporting
confidence: 79%
“…Recent spectroscopic experiments [1][2][3] and theoretical models [4][5][6][7][8][9][10][11][12][13], provide evidence that efficient light harvesting in nature occurs by a quantum mechanism involving sustained electronic coherence [14] and entanglement [15,16] between chromophores. While the chromophores are chlorophyll molecules containing large networks of conjugated carbon bonds that surround a charged magnesium ion, they have largely been represented in theoretical studies [4][5][6][7][8][9][10][11][12][13] by one-electron models that neglect the effects of electron correlation and entanglement within chromophores. Two advanced methods in electronic structure, density-matrix renormalization group [17] and two-electron reduceddensity-matrix theory [18,19], have recently shown that networks of conjugated bonds as in acene chains [17,20], acene sheets [20], and chlorophyll are associated with polyradical character that cannot be adequately described without a strongly correlated many-electron quantum model.…”
Section: Introductionmentioning
confidence: 99%
“…(2) for the extended Hubbard model (see Supplemental Material [11]). Local recombination was added to this effective model via a Markovian quantum dissipation process, appropriate for the super-Ohmic large-bias limit [25] (see Supplemental Material [11]), that incoherently drives only the transition j0i → jgiat a bare rate Γ. This effective model reveals that even the addition of one ionized holon-doublon state j1i which is unaffected by the decay, i.e., taking L ¼ 1, causes the suppression of the actual decay rate Γ eff to jgi from the bare rate Γ as…”
Section: Fig 5 (Color Online)mentioning
confidence: 99%
“…In contrast, despite their attraction in terms of simplicity, intuitive physical insight and efficiency, standard (e.g., Redfield) master equations are often invalid in regimes relevant to molecular complexes due to their limitation to weak system-environment couplings. 53,54 Though procedures such as the polaron transformation can be used to broaden the range of validity of Redfield master equations, [55][56][57][58][59][60][61][62][63] again be restricted, for example, to situations in which the high-frequency environmental response dominates. 57,[64][65][66] Recently, a master equation approach based on the reaction coordinate (RC) model (see Fig.…”
Section: Introductionmentioning
confidence: 99%